A NEW SPECIES OF FREYCINETIA (PANDANACEAE) FROM JAMBI, SUMATRA, INDONESIA - Widjaja, Elizabeth Anita; Pasaribu, Nursahara; Hidayat, Arief (Research Center for Biology, 2009)
WIDJAJA, E.A., PASARIBU, N., HIDAYAT, A. 2009. A new species Freycinetia (Pandanaceae) from Jambi, Sumatra, Indonesia. Reinwardtia 12 (5): 441â442. â Freycinetia berbakensis Widjaja, Pasaribu & Hidayat is proposed as a new species.